A Comparative Study of Committee’s Reports on Corporate Governance in India - Manisha sharma; Dr. Anita Rana (HM Journals, 2022)
After the corporate world distorted due to various scandals, magnitude of corporate governance has been increasing continuously. Corporate Governance is termed as a detailed disclosure of information and an account of an organization’s economic situation, performance, proprietorship and governance, relationship with shareholders and obligation to business ethics and values. Corporate governance acts as a link between shareholders, stakeholders, and board of directors. It should be able to rebuild the trust and confidence of management and the company to the shareholders in the company. From 1991 to till today, corporate governance has gone through many stages for example committees were formed, new rules, regulations, acts, or revised laws came into existence. Since 1991 corporate governance has continuously been evolved to increase transparency,to match with world’s standard, improve and provide strength to companies in India to withstand with world’s companies. The main objective of this research paper is to analyse and compare various committee’s recommendations on corporate governance in India from Indian’s perspective, reports of SEBI and MCA were used for the comparison .